Synthesis, Spectral Study and Theoretical Treatment of Some Transition Metal Complexes of 5-(4-Nitro Phenyl)-4-Amino-3-Mercapto Propenyl-1,2,4-Triazole Ligand - Alias, Mahasin; Seewan, Ameena N; Khalil, Sura; Shakir, Carolin (Al-Nahrain Journal of Science, 2018)
In the present work, we synthesized a series of metal complexes of Co(II), Ni(II), Cu(II), Zn(II) and Au(III) from newly synthesized ligand 5-(4-Nitro Phenyl)-4-Amino-3-Mercapto Propenyl-1,2,4-Triazole (L) in alcoholic medium. These compounds were characterized by several techniques using FT-IR, UV-Visible spectrophotometer, thermal gravimetric TG analyses, magnetic susceptibility, Flame Atomic Absorption technique, elemental analysis and conductivity measurements. From the spectral studies, an octahedral monomer structure was proposed for all complexes except Cu(II) complex has dinuclear structure. The nature of the complexes formed in ethanolic solution has been studied following the molar ratio method and the result recorded 1:1 molar ratio for all complexes. Semi-empirical methods (ZINDO/1, ZINDO/S and PM3) were carried out to evaluate the heat of formation ∆H˚f, binding energy ∆Eb, and dipole moment for all complexes expect Au(III) complex that used AMBER method, also the vibration frequencies and electronic transitions were calculated for prepared ligand to make comparison with experimental results. Electrostatic potential, HOMO and LUMO energies for ligand were calculated to determine the reactive sites of new ligand.